The Pengaruh Duta Merek, Kepercayaan dan Iklan terhadap Keputusan Pembelian padaE-commerce Tokopedia (Studi Kasus pada Pengguna E-commerce Tokopedia di Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya) - Rival Aria Putra; Matdio Siahaan (Neolectura, 2022)
This study is to determine the effect of ambassadors, trust and advertising on purchasing decisions on Tokopedia E-commerce. This research is a quantitative study where the object used is a student of the Management Study Program, Faculty of Economics and Business, Ubhara Jaya users of E-commerce Tokopedia. This research was conducted using non-probability sampling with purposive sampling method. And as for the number of samples used is 93, but after distributing the online questionnaire, 112 samples have been obtained and those that are included in the criteria for the last study have been determined for the study the number of 93 samples. While the data analysis technique used is multiple regressionwhich begins with validity and reliability tests, then classical assumption test which contains multicollinearity test, heteroscedasticity test, and normality test. And finally, there is a hypothesis test that uses the t-test. data was processed using IBM SPSS Statistics V23. The results show that: (1) Partially brand ambassadors have nopositive and significant effect on purchasing decisions on E-commerce Tokopedia, (2) partially trust has a positive and significant effect on purchasing decisions on E-commerce Tokopedia, (3) partially advertising hasa positive and significant effect on purchasing decisions on E-commerce Tokopedia.